2004
DOI: 10.4049/jimmunol.173.11.6635
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Gene Therapy Is an Effective Therapeutic Strategy for Hepatocellular Carcinoma in Immunosuppressed Mice

Abstract: Immunosuppressive therapy for organ transplantation is essential for controlling rejection. When liver transplantation is performed as a therapy for hepatocellular carcinoma (HCC), recurrent HCC is one of the most fatal complications. In this study, we show that intratumoral murine IL-12 (mIL-12) gene therapy has the potential to be an effective treatment for malignancies under immunosuppression. C3H mice (H-2k), injected with FK506 (3 mg/kg) i.p., were s.c. implanted with 2.5 × 106 MH134 cells (H-2k) and we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 59 publications
(42 reference statements)
1
47
0
Order By: Relevance
“…The immunosuppressive regimen currently used after liver transplantation, consisting of tacrolimus/cyclosporine and methylprednisolone, reduces adaptive components of cellular immunity (predominantly T cell-mediated immune responses), while maintaining innate components of cellular immunity. 3,38,39 Because immune surveillance against tumors is mediated by both innate and adoptive components of cellular immunity, augmentation of NK cell responses to tumors, which have been thought to play a central role in innate immunity against tumors, might be a promising immunotherapy approach. Several therapeutic cytokines including IL-2 and IFNs primarily act through NK cells, and many studies have shown that activation of NK cell differentiation and function leads to a more efficient elimination of tumor growth [5][6][7][8][9] ; however, the systemic administration of those cytokines is likely associated with an acceleration of alloimmune responses leading to liver allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive regimen currently used after liver transplantation, consisting of tacrolimus/cyclosporine and methylprednisolone, reduces adaptive components of cellular immunity (predominantly T cell-mediated immune responses), while maintaining innate components of cellular immunity. 3,38,39 Because immune surveillance against tumors is mediated by both innate and adoptive components of cellular immunity, augmentation of NK cell responses to tumors, which have been thought to play a central role in innate immunity against tumors, might be a promising immunotherapy approach. Several therapeutic cytokines including IL-2 and IFNs primarily act through NK cells, and many studies have shown that activation of NK cell differentiation and function leads to a more efficient elimination of tumor growth [5][6][7][8][9] ; however, the systemic administration of those cytokines is likely associated with an acceleration of alloimmune responses leading to liver allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Murine malignant melanoma B16F1 and B16F10 cells were purchased from American Culture Collections (ATCC). MH134, a murine hepatocellular carcinoma cell line, and X5563, a plasmacytoma cell line derived from C3H/HeN mice, were maintained as described (17). An NKsensitive lymphoma cell line, YAC-1, and a T cell lymphoma cell line of C57BL/6 mice origin, EL-4, were also purchased from ATCC.…”
Section: Mice and Tumor Cell Linesmentioning
confidence: 99%
“…S2). 5 Harada et al used 10 pulses of a higher voltage (150 V/cm) and duration (50 ms) to deliver murine interleukin-12 plasmid injected into hepatocellular carcinomas using the same electroporator (CUY 21, Nepa Gene Co., Ltd.) but different electrodes consisting of a pair of needles (36). They applied severer electroporation conditions than ours because of the quite high resistance (1,620 F 90 V) in hepatocellular carcinomas with their needle-type electrodes (37).…”
Section: Discussionmentioning
confidence: 99%